Effect of Monthly, High‐Dose, Long‐Term Vitamin D Supplementation on Central Blood Pressure Parameters: A Randomized Controlled Trial Substudy. Issue 10 (24th October 2017) - Sluyter, John D.; Camargo, Carlos A.; Stewart, Alistair W.; Waayer, Debbie; Lawes, Carlene M. M.; Toop, Les; Khaw, Kay‐Tee; Thom, Simon A. McG.; Hametner, Bernhard; Wassertheurer, Siegfried; Parker, Kim H.; Hughes, Alun D.; et al.
Abstract : Background: The effects of monthly, high‐dose, long‐term (≥1‐year) vitamin D supplementation on central blood pressure (BP) parameters are unknown. Methods and Results: A total of 517 adults (58% male, aged 50–84 years) were recruited into a double‐blinded, placebo‐controlled trial substudy and randomized to receive, for 1.1 years (median; range: 0.9–1.5 years), either (1) vitamin D3 200 000 IU (initial dose) followed 1 month later by monthly 100 000‐IU doses (n=256) or (2) placebo monthly (n=261). At baseline (n=517) and follow‐up (n=380), suprasystolic oscillometry was undertaken, yielding aortic BP waveforms and hemodynamic parameters. Mean deseasonalized 25‐hydroxyvitamin D increased from 66 nmol/L (SD: 24) at baseline to 122 nmol/L (SD: 42) at follow‐up in the vitamin D group, with no change in the placebo group. Despite small, nonsignificant changes in hemodynamic parameters in the total sample (primary outcome), we observed consistently favorable changes among the 150 participants with vitamin D deficiency (<50 nmol/L) at baseline. In this subgroup, mean changes in the vitamin D group (n=71) versus placebo group (n=79) were −5.3 mm Hg (95% confidence interval [CI], −11.8 to 1.3) for brachial systolic BP ( P =0.11), −2.8 mm Hg (95% CI, −6.2 to 0.7) for brachial diastolic BP ( P =0.12), −7.5 mm Hg (95% CI, −14.4 to −0.6) for aortic systolic BP ( P =0.03), −5.7 mm Hg (95% CI, −10.8 to −0.6) for augmentation index ( P =0.03), −0.3 m/s (95% CI, −0.6 to −0.1) for pulse wave velocity ( P =0.02), −8.6 mm Hg (95% CI, −15.4 to −1.9) for peak reservoir pressure ( P =0.01), and −3.6 mm Hg (95% CI, −6.3 to −0.8) for backward pressure amplitude ( P =0.01). Conclusions: Monthly, high‐dose, 1‐year vitamin D supplementation lowered central BP parameters among adults with vitamin D deficiency but not in the total sample. Clinical Trial Registration: URL:http://www.anzctr.org.au . Unique identifier: ACTRN12611000402943.